Genetic differentiation between subpopulations of Swedish mountain (Fjäll and Fjällnära) cattle. (2nd April 2020) - Johansson, Anna M.; Upadhyay, Maulik; Strandberg, Erling; Eriksson, Susanne
ABSTRACT: The Swedish Mountain (Fjäll) cattle and the subpopulation Fjällnära originates from northern Sweden. They are differentiated from both traditional and commercial cattle from southern Sweden. We analysed data from the GGP HD150k SNP array and investigated genetic diversity and differences between Fjäll and Fjällnära, and between different groups of Fjällnära. We found that the Fjällnära can be divided into four groups, which are differentiated from each other and from the other Fjäll cattle. We also compared allele frequencies between different groups of Fjäll and Fjällnära for some of the functional SNPs included in the SNP array. Interestingly, the B allele of Beta lactoglobulin has a very high frequency (94%) in the Fjällnära cattle, which is significantly different from the frequency in the Fjäll cattle (60%). Comparing older samples of Fjäll cattle with more recent samples, we found a significant increase in the frequency of the B allele in Fjäll cattle.